Implementation of Academic Management at the As-Siddiq Kie Raha Islamic Institute (IAI) North Maluku - Wachyudi Eksan; Harol Lumapow; Jeffry SJ Lengkong (International Journal on Integrated Education, 2022)
In managing an educational institution, a representative academic administration management system is needed that is able to manage and provide data and information within the scope of educational institutions, namely to manage curriculum data, manage data on courses offered in semesters, manage class schedules, and plan student studies. , management of student grades, management of student attendance, management of facilities and infrastructure as well as academic information and resources available at the university. This research was conducted at the As-Sidiq Kie Raha Institute of Islam (IAI) North Maluku located in Ternate City. Data analysis in this research is analysis using three general approaches or implementations. In this implementation there are 3 components of interactive model analysis, namely data reduction, data display, and conclusion drawing/verification. Based on several research findings and discussion, the following conclusions can be drawn: 1. Implementation of academic management at the As-Siddiq Kie Raha Islamic Institute (IAI) North Maluku, is not yet optimal, systematic and directed, there is no standard academic management model for In its application, all of this happens because this university is still new so that the structural officials of the teaching staff and educational staff in their environment do not have experience, understand and understand and obey academic regulations, main tasks and functions, so that academic management does not work as expected by stakeholders